High-Rate Capabilities of Ferroelectric BaTiO3–LiCoO2 Composites with Optimized BaTiO3 Loading for Li-Ion Batteries. (6th October 2015) - Teranishi, Takashi; Yoshikawa, Yumi; Sakuma, Ryo; Okamura, Hirokazu; Hashimoto, Hideki; Hayashi, Hidetaka; Fujii, Tatsuo; Kishimoto, Akira; Takeda, Yasuo
Abstract : Ferroelectric barium titanate, BaTiO3 (BT) was coated on lithium cobaltate, LiCoO2 (LC), as an artificial solid electrolyte interface (SEI), via the simple sol–gel route. The high charge–discharge rate capabilities of the composite cathodes were evaluated up to 10C. The LC loaded with l mol% of BT had a measured capacity of 146 mAh/g, which was the highest value measured at 10C. This capacity was 78% of its initial value, and was 238% of the capacity of bare LC over the same number of cycles.